1987
DOI: 10.1016/0306-4522(87)90087-x
|View full text |Cite
|
Sign up to set email alerts
|

Co-localization of tachykinins and calcitonin gene-related peptide in capsaicin-sensitive afferents in relation to motility effects on the human ureter in vitro

Abstract: Tachykinin- and calcitonin gene-related peptide (CGRP) immunoreactivities were localized by immunohistochemistry in the same nerves of the kidney, renal pelvis and ureter as well as in spinal ganglion cells of both the guinea-pig and man. The tachykinin and CGRP-immunoreactive nerves in the ureter were present within the smooth muscle layers, around blood vessels, close to and within the lining epithelium. The levels of neurokinin A-, substance P- and CGRP-like immunoreactivity per tissue weight, as determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
99
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 34 publications
(1 reference statement)
8
99
2
Order By: Relevance
“…This study disclosed few CGRP-IR nerves in the mucosa, sometimes co-running with nitrergic nerves. Such previously reported mucosal distribution [3] further emphasizes the sensory role of CGRP. Moreover, the overlap of NOS-containing innervation with the latter suggests that NO may also be an afferent messenger.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This study disclosed few CGRP-IR nerves in the mucosa, sometimes co-running with nitrergic nerves. Such previously reported mucosal distribution [3] further emphasizes the sensory role of CGRP. Moreover, the overlap of NOS-containing innervation with the latter suggests that NO may also be an afferent messenger.…”
Section: Discussionmentioning
confidence: 78%
“…The sensory neuropeptide CGRP has been considered as a putative candidate for NANC inhibitory neurotransmission in the ureter of various species, including man [3]. This study disclosed few CGRP-IR nerves in the mucosa, sometimes co-running with nitrergic nerves.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…SP and CGRP are colocalized in renal pelvis sensory nerves and may be totally depleted after CAP treatment (Hua et al, 1987). CGRP perfused into the renal pelvis causes an increase in ARNA, which is blocked by a NK1 receptor antagonist .…”
Section: Introductionmentioning
confidence: 99%
“…This nature was designated as "dendritic secretion" by FUJITA et al (1988). It has been recently shown that sensory neurons containing CGRP and SP in the genitourinary tract release these peptides from their dendrites after the application of capsaicin (HUA and LUNDBERG, 1986;HUA et al, 1987;AMANN et al, 1988;SANTICIOLI, et al, 1988). Concerning the mechanism of the dendritic secretion, i. e., "efferent" function of the afferent nerve fibers as proposed in peripheral SP/CGRP-containing nerve fibers, the following two hypotheses have been put forth (ISHIDA-YAMAMOTO and TOHYAMA, 1989): 1) A mechanism via an axon reflex; in which a free nerve ending receives stimulation, which is a conferred to an axon collateral to release signal substances from the varicose portion of the collateral.…”
Section: Endocrine Cellsmentioning
confidence: 99%